Adjunctive antidepressant prescriptions for hospitalized patients with schizophrenia in Asia (2001–2009). (29th August 2012) - Xiang, Yu‐Tao; Ungvari, Gabor S.; Wang, Chuan‐Yue; Si, Tian‐Mei; Lee, Edwin H.M.; Chiu, Helen F.K.; Lai, Kelly Y.C.; He, Yan‐Ling; Yang, Shu‐Yu; Chong, Mian‐Yoon; Tan, Chay‐Hoon; Kua, Ee‐Heok; et al.
Abstract Introduction Little is known about the prescription patterns of adjunctive antidepressants in Asian schizophrenia patients. This study aimed to examine trends in the use of antidepressants and their demographic and clinical correlates in the treatment of schizophrenia in Asia between 2001 and 2009. Methods A total of 6, 761 hospitalized schizophrenia patients in nine Asian countries and territories were examined: 2, 399 in 2001, 2, 136 in 2004 and 2, 226 in 2009. Patients' socio‐demographic and clinical characteristics and prescriptions of psychotropic drugs were recorded using a standardized protocol and data collection procedure. Results The proportion of antidepressant prescription was 6.8% in the whole sample; 5.3% in 2001, 6.5% in 2004 and 8.7% in 2009. There were wide inter‐country variations at each survey ranging from 0.9% in Hong Kong to 15.3% in Singapore in 2001; from 1.9% in Korea to 15.4% in Singapore in 2004; and from 2.7% in Japan to 22.0% in Singapore in 2009. Multiple logistic regression analysis of the whole sample revealed that patients on antidepressants were younger, more likely to receive benzodiazepines and have significant extrapyramidal side‐effects and less likely to have significant positive symptoms. Discussion Unlike findings in Western countries, adjunctive antidepressant prescription for schizophrenia was not common in Asia. The frequency of antidepressant prescription varied among countries and territories, suggesting that a host of clinical and socio‐cultural factors played a role in determining antidepressant use in Asia.